The Incidence of Helminthiasis in Cattle in The Work Area of UPT. Laboratorium Kesehatan Hewan in East Java Province in 2017-2018 - Aulia Nur Afifah; Iwan Syahrial Hamid; Mirni Lamid; Agung Budianto Achmad (Universitas Airlangga, 2020)
Background: The needs of Indonesian people for animal protein from meat are still quite high, but the fulfillment of meat demand has not been sufficient. Many obstacles faced by farmers in developing their livestock business, one of which is helminthiasis. Helminth infections can occur due to feed problems or poor maintenance management. Helminth infestation in the digestive tract can cause intestinal mucosal damage, which can reduce the efficiency of food absorption, causing livestock productivity losses in body weight, milk production, quality of meat, skin, and innards. Purpose: This study aimed to determine the prevalence of helminthiasis and the type of helminths that infected cattle in UPT. Laboratorium Kesehatan Hewan Provinsi Jawa Timur. Method: This study used sedimentation and Whitlock floating method. Result: The highest prevalence in 2017 occurred in Tuban City, which was 6,69%, while the lowest was in Gresik Regency, which was 0%. Whereas in 2018, the highest prevalence occurred in Lamongan City, which was 9,42% and the lowest prevalence in Ngawi Regency, which was 0,22%. The type of helminth that infects the cattle the most in 2017 is Fasciola sp. as many as 114 cases, with the highest number occurring in Magetan Regency, which was 44 cases. In 2018, Fasciola sp. also the most common type of helminth found to infect cattle in 202 cases, with the highest number occurring in Magetan and Pacitan Regency, which was 34 cases.